ON THE INTERPRETATION OF CRYSTAL SIZE DISTRIBUTIONS IN MAGMATIC SYSTEMS - Marsh B.D. (My University, 1998)
The observation that basic igneous rocks most commonly are holocrystalline under a wide spectrum of cooling regimes implies that cooling and crystallization can be uncoupled and considered separately. This is tantamount to realizing that the Avrami number is large in most igneous systems. Crystallization automatically adjusts through nucleation and growth to the cooling regime, and all aspects of the ensuing crystal population reflect the relative roles of nucleation and growth, which reflect the cooling regime. The characteristic scales of crystal size, crystal number and crystallization time are intimately tied to the characteristic rates of nucleation and growth, but it is the crystal size distributions (CSDs) that provide fundamental insight on the time variations of nucleation and growth and also on the dynamics of magmatic systems. Crystal size distributions for batch systems are calculated by employing the Johnson–Mehl–Avrami equation for crystallinity related to exponential variations in time of both nucleation and growth. The scope of the CSD is set by the difference a – b , where a and b are exponential constants describing, respectively, nucleation and growth. The batch CSD has constant slope and systematically migrates to larger crystal size (L) with increasing crystallinity. The diminution in nucleation with loss of melt is reflected in the CSD at late times by a strong decrease in population density at small crystal sizes, which is rarely seen in igneous rocks themselves. Observed CSDs suggest that a – b ∼6–10 and that b ∼0). That is, growth rate is approximately constant and nucleation rate apparently increases exponentially with time. Correlations among CSD slope, intercept, and maximum crystal size for both batch and open systems suggest that certain diagnostic relations may be useful in interpreting the CSD of comagmatic sequences. These systematics are explored heuristically and through the detailed examination of comagmatic CSDs in a number of igneous and industrial systems including, amongst other, Makaopuhi lava lake, Atka volcanic center, Peneplain sill, Dome Mountain lavas, Shonkin Sag lacolith, and Kilauea Iki lava lake. None of these systems shows CSDs typical of purely batch or purely open systems, even when the system itself is known on independent grounds to be a batch system. Instead, the CSDs of each system reflect a combination of kinetic and dynamic influences on crystallization. Heterogeneous nucleation and annexation of small crystals by larger ones, entrainment of earlier grown and ripened crystals, rate of solidification front advance, and protracted transit of a well-established mush column are some of the effects revealed in the observed CSDs. There may be an overall CSD evolution, reflecting the maturity of the magmatic system, from simple straight nonkinked CSDs in monogenetic systems to multiply kinked, piecewise continuous CSDs on well-established systems such as Hawaii and Mount Etna. This is not unlike the evolution of CSDs in some industrial systems. Finally, the fact that comagmatic CSDs are not often captured evolving systematically through large changes in nucleation rates, even in low crystallinity systems, may suggest that magma is always laced with high population densities of nuclei, supernuclei, and crystallites or clusters that together set the initial CSD at high characteristic population densities. Further evolution of the CSD occurs through sustained heterogeneous nucleation and rapid annealing at all crystallinities beginning at the liquidus itself and operating under more or less steady (not exponentially increasing) rates of nucleation.